2021
DOI: 10.1186/s12877-021-02444-y
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and responsiveness of the Frailty Index and Frailty Phenotype in older hospitalized patients

Abstract: Background There is growing interest for interventions aiming at preventing frailty progression or even to reverse frailty in older people, yet it is still unclear which frailty instrument is most appropriate for measuring change scores over time to determine the effectiveness of interventions. The aim of this prospective cohort study was to determine reproducibility and responsiveness properties of the Frailty Index (FI) and Frailty Phenotype (FP) in acutely hospitalized medical patients aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
2
5
0
Order By: Relevance
“…Test–retest reliability of the FI over multiple 14-day periods was ICC = 0.88, which is slightly above the results reported for stable hospital patients over 3 months (ICC = 0.84/0.85) ( 29 ). Our estimate also compares favorably with the range of test–retest ICCs reported for other frailty instruments, for example, 0.65/0.77 for phenotypic frailty over 3 months ( 29 ), 0.71 for the FRAIL scale over 7–15 days ( 46 ), and 0.88 for the Tilburg Frailty Indicator over 10–25 days ( 47 ). In sum, test–retest reliability, as well as internal consistency of the FI were good, and hence the FI can be considered a high-quality instrument for risk stratification among older adults.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…Test–retest reliability of the FI over multiple 14-day periods was ICC = 0.88, which is slightly above the results reported for stable hospital patients over 3 months (ICC = 0.84/0.85) ( 29 ). Our estimate also compares favorably with the range of test–retest ICCs reported for other frailty instruments, for example, 0.65/0.77 for phenotypic frailty over 3 months ( 29 ), 0.71 for the FRAIL scale over 7–15 days ( 46 ), and 0.88 for the Tilburg Frailty Indicator over 10–25 days ( 47 ). In sum, test–retest reliability, as well as internal consistency of the FI were good, and hence the FI can be considered a high-quality instrument for risk stratification among older adults.…”
Section: Discussionmentioning
confidence: 50%
“…(3) Measurement error, finally, is relevant for frailty monitoring, that is, to differentiate “real” frailty changes from error or “noise,” and can be assessed with the standard error of measurement (SEM) ( 27 ). To date, only 2 studies ( 28 , 29 ) provide estimates of the reliability of the standard clinical FI ( 30 ). Based on a large cross-national sample of community-dwelling older adults and confirmatory factor analysis (CFA), Mayerl and colleagues ( 28 ) reported internal consistency (omega) of 0.89–0.93.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The much lower prevalence may be explained by the fact that included patients were almost all functionally independent compared to our study population consisting of comorbid patient with a limited functional score. Moreover, the frailty phenotype in the study of Feenstra et al ( 26 ) was solely based on self-reported items possibly underestimating frailty whereas the frailty phenotype in our study included clinical measures such as gait speed and grip strength.…”
Section: Discussionmentioning
confidence: 92%
“…Some studies reported very similar prevalence, such as Bieniek et al who described a prevalence of 54.2% based on the Fried frailty phenotype in geriatric inpatients ( 25 ) or Chong et al described a 50.0% prevalence based on the FRAIL scale ( 11 ). However, there are also studies that reported a lower prevalence, such as 19% based on a frailty phenotype defined as self-reported items of weight loss, exhaustion, slowness, weakness, and low physical activity in hospitalized medical patients aged 70 years and older ( 26 , 27 ). The much lower prevalence may be explained by the fact that included patients were almost all functionally independent compared to our study population consisting of comorbid patient with a limited functional score.…”
Section: Discussionmentioning
confidence: 99%